Clinico-pathological analysis of Odontogenic Tumors over 28-year-period in Benghazi, Libya - Hamed, Samar S. Saleh; El-Hasi, Nagla S. (Libyan Journal of Dentistry, 2023)
Background: Odontogenic tumors (OTs) are rare lesions that unique to the jaws constituting about < 1% of all oral tumors. They are a complex group of heterogeneous behavior that range from tumor like lesions, benign tumors to malignant neoplasms with potential to metastases. Aim of study: To describe the relative incidence of odontogenic tumors (According to World Health Organization classification 2022) at Oral Pathology Department in Benghazi and compare the finding with the literatures. Methods: A retrospective study of 106 OTs was documented for the demographic data. Statistical analysis was carried out by software SPSS. Results: OTs constituted 1.2% of all diagnosed oral lesions with 97% of them were benign tumors. Ameloblastoma was the most common type (37.7%) followed by odontomas (24.5%). The peak incidence was around the third decade with male: female ratio 1:1.12. mandible was the most common site (64%). Conclusion: OTs are relatively uncommon lesions among our sample that is similar to other literatures with some variations.